Cervical cancer. Results of treatment with Cobalt 60 and deep Roentgenteraphy - Torpoco Ortíz, Jesús (1969)
The study of 1,173 cancer cases registered in two years and trotados parallel with Cobalt-60 and Roentgen-Radium Radium is presented. In both treatment modalities , the dose and the technical procedure were equivalent. The selection of patients was only considering how external conformation of the patient (obese patients were compulsorily treated with Cobalt 60 ) and the availability of time on the cobalt unit . It has been found that only 75 % of patients receiving appropriate and comprehensive treatment ( the other percentage 110 receives for reasons beyond the department) and 62% of it ( 75%) out of sight , ie , are not controlled at 5 years . The therapeutic results can only be studied and compared with similar and each other, taking into account the figures , since the absolute results give a false assessment of the therapeutic value of radiation unfavorably because the quota of patients lost sight is very large . Another aspect worth mentioning is the epidemiological factor in the origin of the high incidence of cervical cancer , the provincial women have the highest rate of this neoplasm.